ROLE OF PREVENTION IN PHYSIOTHERAPY TO INTEGRATE CHILDREN WITH EXTRAPYRAMIDAL SYNDROME - Marcu Vasile; Hodorca Raluca Mihaela; Necula Dana (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Prevention in physical therapy is an integral part of therapy that aims prevention and not treating certain diseases.On the extrapyramidal syndrome, methods and techniques of physical therapy are a preamble of the therapy that has as purpose in the achievement of tangible engrams as close to that of healthy children. Physical therapy with all its aspects of prevention, therapy and rehabilitation achieved by its essence, have an holistic approach to the individual, in this case, of the inexperienced and frightened child by the syndrome pathology. Medical recovery is designed to study neuromuscular and joint mechanisms that will provide to the pacient an normal vigilance activity while driving to recording, analyzing and correcting the deficit. The objectives of physical therapy are subject to a constant process of analysis and synthesis based on the child's mental and physical condition. Methods: Prevention in physical therapy, is studying the optimization of health and prevention for this disability, aggravation of the normal functioning of the body, using techniques and neuro-motor methods. On disabled children the prevention of physical aims to promote: relaxation, sensitivity rehabilitation, correct posture and body alignment with its segments, education / rehabilitation / restoration of control, coordination and balance, respiratory rehabilitation, increased training effort, recovery of joint mobility by handling, increased muscle strength in children aged 3 years and increase muscle strength over 7 years. Results: The assessment results have responded immediately validating that the methods and techniques used helped on extrapyramidal syndrome child. Prevention of physical therapy is therefore an accumulation of information, tools and conclusions, which however will not prevent disability, but prepare the children for integration into society.